SAT0632 Impact of lumbar spine morphology (scoliosis) on early spondyloarthritis pattern (the impala-desir study). (15th June 2017) - Voirin-Hertz, M; Alegria, G Carvajal; Garrigues, F; Simon, A; Feydi, A; Bruin, F de; Reijnierse, M; Heijde, D van der; Loeuille, D; Claudepierre, P; Marhadour, T; Saraux, A; et al.
Abstract : Objectives: To evaluate the impact of scoliosis on both clinical presentation and lumbar imaging of early inflammatory back pain suggestive of spondyloarthritis. Methods: The DESIR cohort is a prospective longitudinal cohort study of adults aged 18–50 with inflammatory back pain (IBP) ≥3 months, ≤3 years. Baseline lumbar X-Rays of patients included in DESIR cohort were read by two central blinded fellow readers (and a rheumatologist spine specialist in case of discrepancy) for presence or not of scoliosis (defined as a Cobb angle>10° and a Nash Moe grade≥1). Associations between scoliosis and baseline clinical variables, presence of X-Rays (New York) and MRI (ASAS and MORPHO proposal definition) sacroiliitis, presence of spinal signs of spondyloarthritis (mSASSS, BASRI-total, SPARCC scores), presence of spinal degenerative MRI signs on X-rays (yes or no) and MRI (presence of Modic abnormalities, Pfirrmann score, Canal stenosis, Extrusion, High intensity zone Facet osteoarthritis) according to central reading (two readers) and axSpA diagnostic confidence (according to local clinician's confidence on a 0–10 visual analogic scale) were assessed by univariate analysis using the chi-square test (or Fisher's exact test where appropriate) and the Mann-Whitney test. Adjustment for multiple testing was performed according to Bonferroni method. Results: 675 patients (47.1% men, mean age of 33.6 years, 89.6% had lumbar pain, 65% fulfilling ASAS criteria) were studied. The mean Cobb angle was 3.2° (± 4.8) and 49/675 (7.3%) patients had lumbar scoliosis. The only significant difference was the lumbosacral sagittal balance. Indeed, scoliotic patients had greater lumbar lordosis (57.8° versus 50.9°; p<0.001) than non-scoliotic. About MRI findings, spinal degenerative manifestations were very scarce in both groups. The major part of degenerative changes was in the two last lumbar discs and vertebras, without significant difference between scoliotic and non-scoliotic patients. Conclusions: Scoliotic patients with inflammatory back pain suggestive of spondyloarthritis do not have more lumbar degenerative lesions than non-scoliotic patients, nor difference of clinical presentation, but they have greater lumbar lordosis. Disclosure of Interest: None declared